Utility of 6% hydroxyethyl starch 130/0.4 in oral cancer surgeries with a duration of over 6 hours: A retrospective case-control study. Issue 7 (17th February 2023) - Yaguchi, Erika; Ujita, Tomoaki; Hamaguchi, Shinsuke
Abstract : To evaluate the utility of 6% hydroxyethyl starch (HES) 130/0.4 in oral cancer surgeries with durations over 6 hours. Using a case-control study design, the investigators enrolled patients who underwent oral cancer surgery involving osteotomy or manipulation near the major blood vessels at the Department of Orofacial Surgery in our hospital between 2017 and 2020. The predictor variable was 6% HES130/0.4. Outcomes included in-out balance and other postoperative parameters pertaining to circulatory maintenance (blood loss, urine volume, infusion volume, blood transfusion volume, albumin dose, hemoglobin levels, blood albumin levels, and doses of vasopressors used to maintain blood pressure), as well as pre- and postoperative renal function, pH, bicarbonate levels, and base excess. Changes in renal function were evaluated by assessing blood urea nitrogen and creatinine levels before surgery and at 1 and 7 days postoperatively. The Mann–Whitney U test was used for between-group comparisons, and Student t test was used for intragroup comparisons. The statistical significance was set at P < .05. A total of 65 patients underwent oral cancer surgery with a duration over 6 hours during the study period. The administration of 6% HES130/0.4 at 22.1 ± 7.5 mL/kg/day did not increase blood loss or the blood transfusion volume. Moreover, patients who were administered 6% HES130/0.4 had a significantly larger mean urine volume and infusion volume than those who were not administered 6% HES130/0.4. The infusion therapy could maintain the urine volume and did not worsen renal function. The results of this study showed that administration of 6% HES130/0.4 at a dose lower than 25 mL/kg in patients undergoing oral cancer surgery over 6 hours was effective for circulation maintenance but did not increase the intraoperative blood loss or transfusion volume. This treatment did not cause any dilutional metabolic acidosis or renal dysfunction.